KEANEKARAGAMAN KARANG DI ZONA LITORAL PERAIRAN IBOIH KECAMATAN SUKAKARYA KOTA SABANG - Samsul Kamal; Nursalmi Mahdi; Humaira , (Biotik, 2015)
A research on " Coral Diversity in Iboih Aquatic Littoral Zone at Sukakarya District of Sabang City " has been conductedfrom 25 to 27 of May 2013.This study aims to find out the coral species and its diversity index on Iboih aquatic littoral zone at Sukakarya District of Sabang City. The datawere collected by using direct observation and non- destructive sampling techniquesusing transect methods Quadrat and Line Transect method. Physical andchemical factors were measuredincluding temperature, pH , salinity, brightness and depth.The results showed that there were 38 species out of 14 familia of coral found on Iboih aquatic littoral zone at Sukakaryadistrict of Sabangcity. The diversity Index of coral in Iboih aquatic littoral zone at Sukakarya district of Sabangcitywas high (Ä¤=3.28).